PENGARUH IKLIM ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP LOYALITAS KARYAWAN DI HOTEL “BINTANG LIMA” PEKANBARU - Suryani Situmorang; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the effect of organizational climate and organizational commitment to employee loyalty partial and simultaneous. This study used a questionnaire as a data collection tool that is distributed to 26 respondents to the employees of the hotel "Bintang Lima" Pekanbaru. Data were then processed using descriptive analysis and statistical analysis using SPSS 23 to test the validity, reliability test, simple linear regression, multiple linear regression analysis, analysis of determination (R2) and hypothesis testing with a test t (partial) and F test (simultaneous ).            The results showed that test result The first hypothesis that organizational climate on employee loyalty is ttest results count (5.838) > ttable (2.062), which means that organizational climate significantly influence employee loyalty. Second, organizational commitment, namely ttest results count (5.883)> ttable (2.062), which means that organizational commitment significantly influence employee loyalty. Ftest results count (41.966)> Ftable (3.42) means the organizational climate and organizational commitment simultaneously significant effect on employee loyalty.  Keywords: Organizational Climate, Organizational Commitment, Employee Loyalty